Airway Elastin is increased in severe asthma and relates to proximal wall area: histological and computed tomography findings from the U‐BIOPRED severe asthma study. Issue 2 (10th January 2021) - Wilson, Susan J; Ward, Jonathan A; Pickett, Helen M; Baldi, Simonetta; Sousa, Ana R; Sterk, Peter J; Chung, Kian Fan; Djukanovic, Ratko; Dahlen, Barbro; Billing, Bo; Shaw, Dominick; Krug, Norbert; et al.
Abstract: Background: Airway remodelling, which may include goblet cell hyperplasia / hypertrophy, changes in epithelial integrity, accumulation of extracellular matrix components, smooth muscle hypertrophy and thickening of the lamina reticularis, is a feature of severe asthma and contributes to the clinical phenotype. Objective: Within the U‐BIOPRED severe asthma study, we have assessed histological elements of airway remodelling and their relationship to computed tomography (CT) measures of proximal airway dimensions. Methods: Bronchial biopsies were collected from two severe asthma groups, one non‐smoker (SAn, n = 28) and one current/ex‐smoker (SAs/ex, n = 13), and a mild‐moderate asthma group (MMA, n = 28) classified and treated according to GINA guidelines, plus a healthy control group (HC, n = 33). Movat's pentachrome technique was used to identify mucin, elastin and total collagen in these biopsies. The number of goblet cells (mucin+) was counted as a percentage of the total number of epithelial cells and the percentage mucin epithelial area measured. The percentage area of elastic fibres and total collagen within the submucosa was also measured, and the morphology of the elastic fibres classified. Participants in the asthma groups also had a CT scan to assess large airway morphometry. Results: The submucosal tissue elastin percentage was higher in both severe asthma groups (16.1% SAn, 18.9% SAs/ex) compared with the HC (9.7%) but did not differ between asthma groups. There was a positive relationship between elastin and airway wall area measured by CT (n = 18–20, rho=0.544, p = 0.024), which also related to an increase in elastic fibres with a thickened lamellar morphological appearance. Mucin epithelial area and total collagen were not different between the four groups. Due to small numbers of suitable CT scans, it was not feasible to compare airway morphometry between the asthma groups. Conclusion: These findings identify a link between extent of elastin deposition and airway wall thickening in severe asthma.